Overview of HIV molecular epidemiology among People who Inject Drugs in Europe and Asia - Nikolopoulos, Georgios K. (Infect Genet Evol, 2016)
HIV strains continuously evolve, tend to recombine and new circulating variants are being discovered. Novel strains complicate efforts to develop a vaccine against HIV and may exhibit higher transmission efficiency and virulence, and elevated resistance to antiretroviral agents. The United Nations Joint Programme on HIV/AIDS (UNAIDS) set an ambitious goal to end HIV as a public health threat by 2030 through comprehensive strategies that include epidemiological input as the first step of the process. In this context, molecular epidemiology becomes invaluable as it captures trends in HIV evolution rates that shape epidemiological pictures across several geographical areas. This review briefly summarizes the molecular epidemiology of HIV among people who inject drugs (PWID) in Europe and Asia. Following high transmission rates of subtype G and CRF14_BG among PWID in Portugal and Spain, two European countries, Greece and Romania, experienced recent HIV outbreaks in PWID that consisted of multiple transmission clusters including subtypes B, A, F1 and recombinants CRF14_BG and CRF35_AD. The latter was first identified in Afghanistan. Russia, Ukraine and other Former Soviet Union (FSU) states are still facing the devastating effects of epidemics in PWID produced by A(FSU) (also known as IDU-A), B(FSU) (known as IDU-B), and CRF03_AB. In Asia, CRF01_AE and subtype B (Western B and Thai B) travelled from PWID in Thailand to neighboring countries. Recombination hotspots in South China, Northern Myanmar, and Malaysia have been generating several intersubtype and inter-CRF recombinants (e.g. CRF07_BC, CRF08_BC, CRF33_01B etc.) increasing the complexity of HIV molecular patterns.